Linking the local vertical variability of permeability and porosity to newly-interpreted lithofacies in the lower Mt. Simon CO2 reservoir. (January 2018) - Ritzi, Robert W.; Ghose, Ritu; Bottomley, Michael; Reesink, Arnold J.H.; Best, Jim; Freiburg, Jared T.; Webb, Nathan D.
Highlights: Local vertical variance in petrophysical attributes is deterministically decomposed, according to sedimentary facies. Factor interactions are quantified. Parsimonious models for petrophysical parameters, linked to facies models, result. The method is illustrated with newly revised data from the lower Mt. Simon Sandstone. Abstract: A full understanding of the subsurface processes relevant to CO2 geo-sequestration, including CO2 movement and trapping, requires establishing basic relationships between the sedimentary architecture in CO2 reservoirs and the associated variations in petrophysical attributes that can affect plume dynamics and residual CO2 trapping. In this context, the variance and covariance of petrophysical attributes of the lower Mt. Simon Sandstone reservoir (Illinois, USA) are quantitatively decomposed according to sedimentary textures and structures that vary among sedimentary facies. Building on Ritzi et al. (2016), the sedimentary facies of the lower Mt. Simon are re-classified with new interpretations of sedimentary structures. A newly-revised methodology is used in which factor interactions are formally quantified and the magnitude of their contribution to the variance is compared to the main-factor effects. The decomposition results show the main-factor effects contributing to the variance of permeability and porosity are the differences in grain-size and the presence or absence of bleaching textures. The differences in permeability or porosity among the newly defined sedimentary structures make a relatively small contribution to the sample variance, and the 2-way and 3-way factor interactions are negligible. Permeability and porosity increase with coarser grain size, independent of the presence or absence of bleaching and independent of sedimentary structure. The presence of bleaching textures reduces permeability and porosity independent of the grain size or sedimentary structure. The general approach and these specific results aid in developing parsimonious reservoir simulation models.